Severidade do mal-do-Panamá da bananeira ‘maçã’ em função de biofertilizantes e isolados de Fusarium oxysporum f. sp. cubense - Silveira, Flávia Aparecida da (2018)
Banana is one of the most important socioeconomic fruits in the world. Among the cultivars produced in Brazil, the preferred by Brazilians is 'Maçã', which is a cultivar that is highly susceptible to Fusarium oxysporum f. sp. cubense (Foc) (Panama desease). The objective of this work was to evaluate the effect of doses of biofertilizers on the in vitro mycelial growth of Foc isolates and to evaluate the contents of chlorophyll a, b and total, DNA content, vegetative growth and the severity of Panama disease in 'Maça' banana tree seedlings treated with different Foc isolates and biofertilizers, in a greenhouse experiment. In the in vitro assay, different doses of the respective biofertilizers were tested: Agro-Mos ® (0.0, 1.0, 2.0, 4.0 and 8.0 mL L -1 ); Compound-Aid ® (0.0, 0.5, 1.0, 2.0 and 4.0 mg L -1 ) and Nem-Out ® (0.0, 2.5, 5.0, 10.0 and 20.0 mg L -1 ) combined with four Foc isolates (CML3487, CML3488, CML3489 and CML3490). The studied variables were: total mycelial growth, rate of growth inhibition and mycelial growth daily. In the greenhouse, the same isolates were tested in combination with Agro-Mos ® , Coppercrop ® , Compost-Aid ® , Nem-Out ® and Compost-Aid ® + Nem-Out ® biofertilizers. The values of chlorophyll, DNA content, height, diameter, total leaf area, number of leaves, fresh and dry shoot mass, fresh and dry mass of roots and severity of disease in the aerial part, in the rhizome, in the vascular system and in the root system were evaluated. The isolates CML3487 and CML3490 presented higher rate of inhibition than the isolates CML3488 and CML3489. The chlorophyll content was higher in 'Maça' banana plants treated with Compost-Aid ® when compared to the control treatment. Plants inoculated with the isolates CML3488 and CML3489 had lower DNA content. The Compost-Aid ® and Nem-Out ® treatments reduced the severity of the Panama disease. It is concluded that the doses of biofertilizers studied in vitro inhibited Foc mycelial growth, except for the 1.0 ml L -1 dose of Agro-Mos ® . The biofertilizers benefited the vegetative growth of the seedlings and did not interfere in the DNA content. However, the DNA content was altered in the plants inoculated with the isolates CML3488 and CML3489. The severity of Panama disease was reduced in plants treated with Compost-Aid ® and Nem-Out ® biofertilizers.